Psychological Impact of Childhood Trauma on Adolescents: A Scoping Review - Mei Putri Crismayanti; Meidiana Dwidiyanti; Anggorowati Anggorowati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Violence experienced in childhood will lead to a period of crisis when a person is in adolescence. The crisis period that arises is unique to adolescence. Some adolescents become increasingly experiencing crises or problems when in childhood they experience an unpleasant event or even trauma. Traumatic experiences in childhood will have their own impact on adolescents. Objektive: This study aims to get a clear picture of the psychological impact of childhood trauma on adolescents. Methods: Researchers use the scoping review method. The literature search was conducted using the search keywords